`int (u + 4)(2u+ 1) du` Find the general indefinite integral.

Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to evaluate the indefinite integral, hence, you need to open the brackets, such that:

`(u+4)(2u+1) = 2u^2 + 9u + 4`

 

`int (u+4)(2u+1) du = int (2u^2 + 9u + 4) du `

`int (u+4)(2u+1) du = int 2u^2 du + int 9u du + int 4du`

 

`int (u+4)(2u+1) du = 2u^3/3 + 9u^2/2 + 4u + c`

Hence, evaluating the indefinite integral yields `int (u+4)(2u+1) du = 2u^3/3 + 9u^2/2 + 4u + c.`